FRI0109 Predicting cardiovascular disease in rheumatoid arthritis: The effect of long-term storage on measured cholesterol levels in frozen serum samples. (23rd January 2014) - Arts, E.; Smith, J.; Arntz, O.; Popa, C.; Semb, A.G.; van de Loo, F.; van Riel, P.; Kitas, G.; Fransen, J.
Abstract : Background: Cardiovascular risk is increased in rheumatoid arthritis (RA) patients. Algorithms for cardiovascular (CV) risk stratification as SCORE or Framingham's score are used in the general population. Before they can be used for (CV) risk assessment in RA, validation by calibration and updating of these algorithms, is needed. It would be an advantage if long lasting RA cohorts could be used for this purpose. However, it is unclear if cholesterol levels in frozen serum samples can be used. There is no data available regarding the validity of cholesterol measurements in samples after long-term storage (>10 years). Objectives: To assess the stability of serum total cholesterol (TC), HDL- and LDL-cholesterol (HDL-c, LDL-c) over time, by estimating the effect of storage time on cholesterol levels in frozen serum samples of RA patients. Methods: In the Nijmegen early RA cohort that started in 1985, non-fasting blood samples were taken annually during follow-up and stored at -20 o C. After thawing in 2011, TC and HDL-c were measured enzymatically. LDL-c was calculated using the Friedewald formula. Serum samples from year 0, 1, 2, 3, 5, 7 and 10, during follow-up were used. The cohort was divided into 5 sub-cohorts, starting at 1985 up to 2009 covering 5 years of calendar time each. Per subcohort, 30 RA patients were randomly selected. The data were analyzed for differences between subcohorts in cholesterol levels using longitudinal regression (linear mixed models) while age, gender, smoking, BMI, blood pressure, statin use, DAS28 score, rheumatoid factor positivity at baseline, were considered potential confounders. Results: In total, 1002 serum samples were used from 152 patients, evenly distributed across sub-cohorts, with a mean±SD age 54±13.8 years, 65% were female and 80% were rheumatoid factor positive. In all sub-cohorts, the course of cholesterol levels over time was non-linear. Age and gender were added to the regression model as covariates with BMI at baseline being the only confounder. There was a significant storage effect for LDL-c levels (p=0.047), but not for TC (fig. 1 ) and HDL-c (p=0.099 and p=0.175 respectively). The differences between the youngest and oldest subcohorts were -0.17 mmol/L/year for LDL-c, -0.17 mmol/L/year for TC, and -0.02 mmol/L/year for HDL-c. Conclusions: There was no storage effect in frozen serum on HDL-c and TC, but there was a significant storage effect on LDL. Although the found effects per additional year of storage are small, over time this effect could accumulate to a clinically relevant change and a correction factor can adjust for this effect. Therefore, serum samples stored for longer periods of time under stable conditions can be considered suitable for cholesterol measurements. Disclosure of Interest: None Declared